Seasonal variation in the abundance and distribution of ticks that parasitize Microcebus griseorufus at the Bezà Mahafaly Special Reserve, Madagascar - Rodriguez, Idalia A. (Int J Parasitol Parasites Wildl, 2015)
At Bezà Mahafaly Special Reserve (BMSR), Madagascar, mouse lemurs (Microcebus griseorufus) are parasitized by multiple species of haemaphysaline ticks. At present we know little about the role ticks play in wild lemur populations and how they can alter interspecies relationships within communities or impact host fitness. In order to better understand these dynamics at BMSR, we examined parasite-host interactions as well as the ecology of mouse lemurs and their infesting ticks, Haemaphysalis lemuris and H. sp. cf. simplex. We show that season, host sex, and habitat influence the relative abundance of ticks on mouse lemurs. Specifically, infestations occur only during the dry season (May–October), are higher in males, and are higher at the study site with the most ground cover and with greater density of large-bodied hosts. Microcebus likely experience decreased susceptibility to tick infestations during the wet season because at that time they rarely if ever descend to the ground. Similarly, male mouse lemurs have higher infestation rates than females because of the greater time they spend traveling and foraging on the ground. During the dry season, Microcebus likely serve as hosts for the tenrec tick, H. sp. cf. simplex, when tenrecs hibernate. In turn, during the wet season when mouse lemurs rarely descend to the ground, other small mammals at the reserve may serve as maintenance hosts for populations of immature ticks. The synchronous development of larvae and nymphs could present high risk for vector-borne disease in Microcebus. This study also provides a preliminary description of the ecology and life cycle of the most common lemur tick, H. lemuris.